Navigating the FDI-energy nexus: a comprehensive framework for sustainable energy futures - Ahmad Khan, Hafizah Hammad; Abdul Ghani, Rosmaiza; Othman, Muhammad Hanif; Handri, Handri; Azib, Azib (Universiti Teknologi MARA, Kedah, 2023)
In today’s globalized world, foreign direct investment (FDI) plays a crucial role in fostering economic growth and the development of nations. However, its implications for energy consumption require careful investigation. Since past studies predominantly explored the aggregate effects of FDI on energy consumption, this study aims to establish a comprehensive framework that provides nuanced insights into the FDI-energy relationship. The proposed framework delves into the sectoral-level effects and the roles of policy approach in assessing the impact of FDI on energy consumption. The framework can be used to examine whether FDI promotes cleaner energy, which economic sectors benefit the most from FDI inflows, and whether a country’s policy significantly influences the FDI-energy dynamic. Hence, this framework will contribute to a more informed decision-making process by shedding light on the complex interplay between foreign investment, energy consumption, and environmental sustainability. With rising environmental awareness, this framework serves as a valuable tool to foster green development and assist countries in achieving sustainable energy futures.